Palliative sedation in Brazil: an integrative literature review - Halfeld, João Carlos (2024)
Palliative sedation integrates the broad spectrum of practices and approaches in palliative care. Its mainobjective is not to anticipate the end of life, but to provide comfort and symptom relief for terminalconditions; however, opinions in academic, professional, social, and religious contexts differ aboutits application. This integrative literature review gathers relevant discussions and research in theBrazilian context to contribute to a more updated and appropriate understanding of palliative sedation.Discussions on palliative sedation bring issues regarding its emergence, the opinions of physicians andstudents, bioethical factors, and challenges. However, the available literature on this topic is scarce,encompassing social, ethical, religious, and professional aspects that require individual interpretationsand consensus among social spheres.